Characterization of the bZIP Transcription Factor Family in Pepper (Capsicum annuum L.): CabZIP25 Positively Modulates the Salt Tolerance - Gai, Wen-Xian; Ma, Xiao; Qiao, Yi-Ming; Shi, Bu-Hang; ul Haq, Saeed; Li, Quan-Hui; Wei, Ai-Min; Liu, Ke-Ke; Gong, Zhen-Hui (Frontiers in Plant Science, 2020)
The basic leucine zipper (bZIP) proteins compose a family of transcription factors (TFs), which play a crucial role in plant growth, development, and abiotic and biotic stress responses. However, no comprehensive analysis of bZIP family has been reported in pepper (Capsicum annuum L.). In this study, we identified and characterized 60 bZIP TF-encoding genes from two pepper genomes. These genes were divided into 10 groups based on their phylogenetic relationships with bZIP genes from Arabidopsis. Six introns/exons structural patterns within the basic and hinge regions and the conserved motifs were identified among all the pepper bZIP proteins, on the basis of which, we classify them into different subfamilies. Based on the transcriptomic data of Zunla-1 genome, expression analyses of 59 pepper bZIP genes (not including CabZIP25 of CM334 genome), indicated that the pepper bZIP genes were differentially expressed in the pepper tissues and developmental stages, and many of the pepper bZIP genes might be involved in responses to various abiotic stresses and phytohormones. Further, gene expression analysis, using quantitative real-time PCR (qRT-PCR), showed that the CabZIP25 gene was expressed at relatively higher levels in vegetative tissues, and was strongly induced by abiotic stresses and phytohormones. In comparing with wild type Arabidopsis, germination rate, fresh weight, chlorophyll content, and root lengths increased in the CabZIP25-overexpressing Arabidopsis under salt stress. Additionally, CabZIP25-silenced pepper showed lower chlorophyll content than the control plants under salt stress. These results suggested that CabZIP25 improved salt tolerance in plants. Taken together, our results provide new opportunities for the functional characterization of bZIP TFs in pepper.